Análisis costo beneficio de la instalación de un sistema de agua ultrapura en el servicio de Farmacotecnia del Hospital Belén de Trujillo - Loyola Mendoza, Lorenzo Ricardo (2017)
The present study has as main objective to determine the cost-benefit of the implementation of a system of ultrapure water in the Service of Pharmacotechnics of the Hospital Belen de Trujillo, through the technique of structured observation, data were collected that have allowed the calculation of the benefits As well as being able to determine the flow of fixed costs and variable costs that correspond to S /. 241,401.77 Soles and S /. 178.437.76 Soles, respectively. The results were estimated by calculating the net present value (NPV), yielding a value of 1.35 and being greater than unity. This indicator means that for each S /. 1.00 invested in the project during the evaluation period (5 years), is recovering approximately S /. 0.35 concluding that the implementation project is profitable in the next 5 years, in addition to increasing the benefits if the production of sterile water is increased for the contribution to third consumers